2018
DOI: 10.1115/1.4040108
|View full text |Cite
|
Sign up to set email alerts
|

Performance Assessments of Organic Rankine Cycle With Internal Heat Exchanger Based on Exergetic Approach

Abstract: This study makes energy and exergy analysis of a sample organic Rankine cycle (ORC) with a heat exchanger which produces energy via a geothermal source with a temperature of 140 °C. R600a is preferred as refrigerant to be used in the cycle. The changes in exergy destructions (of irreversibility) and exergy efficiencies in each cycle element are calculated in the analyses made based on the effectiveness of heat exchanger used in cycle and evaporator temperature changing between 60 and 120 °C for fixed pinch poi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The best working fluid was R123, achieving a maximum exergy efficiency of 57%. Yamankaradeniz et al [32] analyzed the variation in the evaporator effectiveness in a G-ORC, and found that the energy and exergy efficiencies increased up to 6.87% and 6.21%, with the increment of the effectiveness. Invernizzi et al [33] studied a modified ORC including a flashing tank and a mixing chamber, as shown in Figure 7.…”
Section: Single-stage Orcmentioning
confidence: 99%
“…The best working fluid was R123, achieving a maximum exergy efficiency of 57%. Yamankaradeniz et al [32] analyzed the variation in the evaporator effectiveness in a G-ORC, and found that the energy and exergy efficiencies increased up to 6.87% and 6.21%, with the increment of the effectiveness. Invernizzi et al [33] studied a modified ORC including a flashing tank and a mixing chamber, as shown in Figure 7.…”
Section: Single-stage Orcmentioning
confidence: 99%
“…In this validation, only two points at a fixed radial position from the tube external wall, A (r = 3 mm) and B (r = 9 mm), have been considered. The heat transfer model considers the simultaneously solving of Equations ( 1), ( 4) and (5). Equation ( 1) is modified by removing the heat source and adjusting the thermophysical properties of hydrogen to the HTF (water).…”
Section: Model Validationmentioning
confidence: 99%
“…However, ORC and thermoelectric generators convert waste heat to electricity with very low energy efficiency in the range ca. 2-15% [3][4][5][6]. Besides, these methods need to be installed near the waste heat source, which can make the overall installation (e.g., heat source + heat recovery systems) very costly [1].…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, if the heat is available at a constant temperature, therefore the selection of ORC and thermoelectric generators for heat recovery can improve the overall energy efficiency by generating extra electricity to the end-users. On the other hand, if the temperature of the waste heat fluctuates in a small or great range, domestic hot water or steam production using heat exchangers is the viable option [3][4][5][6][7] Although ORCs are attractive for waste heat to work conversion applications, it is noticed that they possess low thermal efficiency of approximately 5-10% [8]. This energy efficiency is greatly improved to 15-30% by identifying and optimizing the parameters affecting their performance [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…It was also shown that the insertion of a recuperator at the downstream of the expander could improve the efficiency to up 30% [11]. However, the improvement of thermal efficiency cannot outweigh the capital cost of the installed ORC components, which make the ORC very prohibitive in Although ORCs are attractive for waste heat to work conversion applications, it is noticed that they possess low thermal efficiency of approximately 5-10% [8]. This energy efficiency is greatly improved to 15-30% by identifying and optimizing the parameters affecting their performance [9,10].…”
Section: Introductionmentioning
confidence: 99%